Jurassic brachyurans of the genus Bucculentum - Krzemińska, Ewa; Starzyk, Natalia; Fraaije, René H. B.; Schweigert, Günter; Lukeneder, Alexander (Zootaxa, 2021)
The genus Bucculentum Schweitzer & Feldmann, 2009 is exceptional among the brachyuran decapods in having the augenrest dorsally inclined. Hitherto, the genus comprised two species, both from European Upper Jurassic localities; here, further two species are described, Bucculentum horstkuscheli, n. sp. and B. plettenbergense, n. sp., which differ in their proportions of the carapace regions and especially in their shapes of the augenrest. A newly described feature shared by all congeneric species is the groove extending from the centre of the dorsal portion of the augenrest and terminating towards the cervical groove. The function of this groove could have been to lead the water stream out from the augenrest to cleanse impurities from the muddy sea bottom, where these crabs are supposed to have lived.